1999
DOI: 10.1088/0022-3727/32/22/311
|View full text |Cite
|
Sign up to set email alerts
|

A two-temperature kinetic model of SF6plasma

Abstract: Studying the influence of thermal departures from equilibrium in SF 6 circuit-breakers, we develop a two-temperature kinetic model to calculate the composition. Such a kinetic approach has not been adopted until now for SF 6 plasma because of the complexity of chemical processes. Our model takes into account the collisional mechanisms responsible for the creation and disappearance of atoms and molecules through 19 species linked by 66 chemical reactions. To solve the conservation equations, the model uses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…highly electro-negative and where negative ions are created at significant amounts. [93][94][95] Nozaki et al 43 of methane in dielectric barrier discharges (DBD) in a packed bed reactor, using a simplified version of the kinetic scheme of Tachibana et al 52 The latter was initially developed for chemical vapour deposition and included 18 positive ions ranging from to . For methane plasmas, it is usually common in…”
Section: Ionsmentioning
confidence: 99%
“…highly electro-negative and where negative ions are created at significant amounts. [93][94][95] Nozaki et al 43 of methane in dielectric barrier discharges (DBD) in a packed bed reactor, using a simplified version of the kinetic scheme of Tachibana et al 52 The latter was initially developed for chemical vapour deposition and included 18 positive ions ranging from to . For methane plasmas, it is usually common in…”
Section: Ionsmentioning
confidence: 99%
“…, NF, NS and 80 reactions, with 76 to be reverse ones. The reactions are obtained from the work of Girard et al [13], Adamec et al [11], Teulet et al [14], Woodall et al [15] and Bartlová et al [10] as shown in table 1.…”
Section: Two-temperature Chemical Kinetic Modelmentioning
confidence: 99%
“…However, prior to the 1T-NCE model for mixed gas plasma, two-temperature chemically non-equilibrium (2T-NCE) model for pure Ar only with ICTP have been developed by Mostaghimi et al [27], Paik et al [28] and Bartosiewicz et al [29]. Gonzalez et al [30,31] developed thermal and chemical non-equilibrium model for SF 6 circuit breaker arcs. So, except Zhao et al a very few works have been done for mixed gas plasma.…”
Section: Two-temperature Non-chemical Equilibrium (2t-nce)mentioning
confidence: 99%
“…The most primary one is the one-temperature chemical equilibrium (1T-CE) model [3] that is widely known as LTE model. The second one is the one-temperature chemical non-equilibrium (1T-NCE) model [31,32]. Two-temperature chemical non-equilibrium (2T-NCE) model for Ar-N 2 ICTP was developed by one of the author before [34].…”
Section: Three Different Models For Thermal Plasma Simulationmentioning
confidence: 99%